UNA NUEVA RATA DE CAMPO TYLOMYS GYMNURUS SAN LUIS POTOSI NOV - VILLA RAMIREZ, BERNARDO (Petróleos Mexicanos, CD MEXICO, DF, MEX, 1942)
One plate Acerentulus tropicum and Sil-vestridia artiochaeta are described
ANS INST BIOL
Keywords: NUEVA RATA DE CAMPO, TYLOMYS GYMNURUS SP NOV; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; RATAS